Pregnancy urinary phenol biomarker concentrations in relation to serum levels of inflammatory cytokines: Results from the EARTH study - Xinxiu Liang; Sarah Grill; Xilin Shen; Paige L. Williams; Tamarra James-Todd; Jennifer B. Ford; Kathryn M. Rexrode; Antonia M. Calafat; Jorge E. Chavarro; Russ Hauser; Lidia Mínguez-Alarcón (Environment International, 2025)
Background: Evidence on the association between maternal phenol exposure and inflammation during pregnancy is limited and inconsistent. Objective: To evaluate associations between urinary phenol biomarkers and serum inflammatory cytokines across pregnancy, and to examine whether associations vary by trimesters. Methods: We included 175 pregnant women from the Massachusetts General Hospital Fertility Center and participating in the Environment and Reproductive Health (EARTH) Study (2005–2017), with available data on urinary concentrations of eight phenol biomarkers and serum inflammatory biomarkers, high-sensitivity C-reactive protein (hsCRP) and interleukin-6 (IL-6). Linear regression models were employed to assess the association between individual phenol biomarker concentrations and log-transformed inflammatory cytokine levels, while Bayesian Kernel Machine Regression (BKMR) models were utilized to evaluate phenol biomarker mixtures. Analyses were further stratified by the trimester of sample collection. Results: Overall, detectable urinary ethylparaben was positively associated with serum hsCRP (β: 0.464; 95 % CI: 0.012, 0.917). In trimester-specific analyses, urinary butylparaben was positively associated with hsCRP (β: 0.533; 95 % CI: 0.006, 1.059) in the first trimester, but negatively associated with IL-6 (β: −0.613; 95 % CI: −1.062, −0.164) in the second trimester. Urinary bisphenol A was inversely associated with hsCRP (β: −0.428; 95 % CI: −0.731, −0.125) in the third trimester. Conclusions: Our findings suggest that exposure to certain phenols may disrupt inflammatory profiles in pregnancy, with effects varying by trimesters. These novel associations underscore the importance of exposure timing when assessing environmental risk factors for maternal and offspring health outcomes.